PHOTOSYNTHESIS AND YIELDS OF GRASSES GROWN IN SALINE CONDITION - Purbajanti, E.D.; Soetrisno, R.D.; Hanudin, E.; Budhi, S.P.S. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
The aim of this study was to know effects of saline condition to crop physiology, growth andforages yield. A factorial completed random design was used in this study. The first factor was type ofgrass, these were king grass (Pennisetum hybrid), napier grass (Pennisetum purpureum), panicum grass(Panicum maximum), setaria grass (Setaria sphacelata) and star grass (Cynodon plectostachyus). Thesecond factor was salt solution (NaCl) with concentration 0, 100, 200 and 300 mM. Parameters of thisexperiment were the percentage of chlorophyll, rate of photosynthesis, number of tiller, biomass and drymatter yield. Data were analyzed by analysis of variance and followed by Duncan’s multiple range testwhen there were significant effects of the treatment. Panicum grass had the highest chlorophyll content(1.85 mg/g of leaf). Photosynthesis rate of setaria grass was the lowest. The increasing of NaClconcentration up to 300 mM NaCl reduced chlorophyll content, rate of photosynthesis, tiller number,biomass yield and dry matter yield. Responses of leaf area, biomass and dry matter yield to salinitywere linear for king, napier, panicum and setaria grasses. In tar grass, the response of leaf area andbiomass ware linear, but those of dry matter yield was quadratic. The response of tiller number tosalinity was linear for all species.